Soil application of Trichoderma harzianum and T. viride on biochemical constituents in bacterial wilt resistant and susceptible cultivars of tomato - BIKASH DAS, J.P. SHARMA*, S. KUMAR and (Indian Phytopathology, 2012)
Biochemical basis of plant defense responses against Ralstonia solanacearum bacterial wilt of tomato due to two Trichoderma species studied.Â Twenty one days old seedlings of resistant (Swarna Lalima) and susceptible (Pusa Ruby) varieties of tomato grown under pot conditions were inoculated with pathogen R. solanacerum (OD 600nm = 0.3abs unit) simultaneously with the suspension cultures of T. harzianum and T. viride. Higher content of total carbohydrate, total phenols, total soluble proteins and total free amino acids in the bacterial wilt resistant plants were recorded indicating their efficacy to be used as marker for resistance against bacterial wilt. The marked increase in the content ofÂ phenol in the stem of R. solanacerum infected plants in response to T. viride consolidated the hypothesis of antagonist- stimulated disease resistance mechanism in tomato against the incidence of bacterial wilt.